Disparities in treatment modalities and survival among older patients with high-grade serous ovarian cancer - Yan Cai; Tong Shu; Hong Zheng (BMC, 2024)
Abstract Background Undertreatment of ovarian cancer is common among older women. We aimed to evaluate the treatment modalities offered to older patients and their impact on overall survival (OS). Methods The study identified 5,055 patients with high-grade serous ovarian cancer and 3584 patients with advanced stage (IIIC + IV) disease from the Surveillance, Epidemiology, and End Results (SEER) database from January 1, 2010, to December 31, 2017. We performed comparisons of OS and ovarian cancer-specific survival (OCSS) across age groups using a Cox proportional hazards model. Results Very elderly patients (≥ 75 years old) received treatment with significantly less surgical complexity, such as no lymphadenectomy (59.7% vs. 48.6%; p < 0.001) and a lower rate of optimal debulking surgery (44.0% vs. 52.7%; p < 0.001), as well as lower rates of chemotherapy (78.2% vs. 89.4%; P<0.001) and standard treatment (70.6% vs. 85%; p < 0.001). High proportions of both very elderly and elderly patients received neoadjuvant chemotherapy (NACT), with no significant difference (38.7% vs. 36.2%; P = 0.212). Patients aged ≥ 75 years had significantly worse OS and OCSS. Conclusion With increasing age, the survival rate of women with ovarian cancer decreases significantly. Noticeably fewer ovarian cancer patients aged over 75 years receive standard treatments, and more very elderly patients are treated with NACT.